Taxonomic revision of Jumellea (Orchidaceae, Angraecinae) in the Mascarenes - Pailler, Thierry; Rakotoarivelo, Fanny Patricka; Razafimandimbison, Sylvain G.; Bytebier, Benny; Florens, F. B. Vincent; Martos, Florent; Baider, Cláudia (Phytotaxa, 2020)
We present a taxonomic revision of the genus Jumellea (Angraecinae; Orchidaceae) in the Mascarenes based on morphological study and field observations. We examined 328 specimens mostly from the MAU, P and REU, and recognise nine species. We provide a key, morphological descriptions, distributions, habitats, phenologies and conservation assessments following the Red List categories and criteria (IUCN). All nine species are present on Réunion with two being endemic there, and five have been confirmed on Mauritius, none of them endemic. The single species recorded for Rodrigues is also the only one found on all three islands of the Mascarenes and Madagascar. Five species are endemic to the Mascarene Archipelago, whereas the other four also occur in Madagascar. All nine species qualify as threatened with extinction on at least one of the islands of the Mascarenes. Two species are probably extinct on one island, and only two species on Réunion are not threatened.